2018
DOI: 10.31219/osf.io/sut7r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Future accessibility impacts of transport policy scenarios: equity and sensitivity to travel time thresholds for Bus Rapid Transit expansion in Rio de Janeiro

Abstract: Highlights• The study estimates how the TransBrasil BRT project in Rio de Janeiro will likely impact employment accessibility for different income groups • The full implementation of the proposed BRT could benefit up to 58% of the city population, increasing job accessibility by 11% on average • This BRT project could promote substantially larger accessibility gains for lower-income groups and reduce inequalities in access to opportunities • The study shows that the conclusions of equity assessments of transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 33 publications
(45 reference statements)
0
16
0
3
Order By: Relevance
“…Due to varying data availability across the study cities, we select the first Wednesday in May after the updating date of GTFS as shown in Table 3. Routing between a given origin-destination pair is conducted using an open-source multi-modal routing engine, OpenTripPlanner (OTP) 62 , similarly used in previous studies 18,63,64 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to varying data availability across the study cities, we select the first Wednesday in May after the updating date of GTFS as shown in Table 3. Routing between a given origin-destination pair is conducted using an open-source multi-modal routing engine, OpenTripPlanner (OTP) 62 , similarly used in previous studies 18,63,64 .…”
Section: Methodsmentioning
confidence: 99%
“…For each pair of origin-destination, OTP finds the fastest door-to-door trip given a set departure time and the combination of transport modes available. The maximum walking distance is set to 800 m. To better balance the errors and the computation time, we use a hybrid sampling approach with 15-min resolution that helps us avoid the Modifiable Temporal Unit Problem (MTUP) 18,35 . The departure times are set to every 15 min from a randomly selected start time until an average weekday is sampled by 96 evenly spaced times.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time of day for which the O-D matrices are calculated is also important to consider, because service levels and transit departure times vary throughout the data. While Pereira (2019) calculated average travel time matrices based on travel at regular intervals throughout the day, Boisjoly and El-Geneidy (2017) showed that calculating accessibility for travel at 8 a.m. only was a reliable indicator of relative accessibility at other times in Toronto. Given our study examines accessibility to hubs, we consider Boisjoly and El-Geneidy’s (2017) single-time approach to reliably reflect commuting dynamics in our study cities.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…Apart from these Olympic areas, other improvements in road infrastructure were carried out in different parts of the city. Transport infrastructure projects promote accessibility gains [89]. However, access inequalities in the city of Rio seem to remain [90].…”
Section: Case Studymentioning
confidence: 99%